PERAN GURU PENGGERAK DALAM MENINGKATKAN KUALITAS PEMBELAJARAN PENDIDIKAN AGAMA HINDU - I Nyoman Kiriana; Ni Nyoman Sri Widiasih; I Gusti Made Widya Sena (Jurnal Penjaminan Mutu, 2022)
Teachers do not only have a role as educators. However, through the driving teacher program, teachers also have a role as agents of change in realizing independent learning in a school climate. The driving teacher must be able to adapt in dealing with various situations that occur in the world of education. The role of the driving teacher in learning Hindu religious education is very strategic and important to improve the quality of learning. In learning Hindu religious education, the driving teacher must be able to shape the character of students with noble character in accordance with local wisdom. The role of the driving teacher in improving the quality of learning for Hindu religious education includes (1) the role of the driving teacher as a leader and facilitator in learning, (2) the role of the driving teacher in encouraging the growth and development of holistic learning, (3) the role of the driving teacher in becoming a trainer for other teachers. , (4) The role of the driving teacher as a swallower and motivator and (5) The role of the driving teacher in collaborating and agents of educational transformation. The role of the teacher will not be replaced by technology, even though various learning resources exist in today's digital technology. Because technology cannot sort out and teach good and bad things to students. While the teacher is able to educate, set an example and teach which things are good and bad things to do. Hindu religious teachers play an important role in the formation of noble character and student character.